ANALISIS KINERJA WIRELESS DISTRIBUTION SYSTEM (WDS) (STUDI KASUS: DINAS KESEHATAN KOTA PALEMBANG) - Aan Restu Mukti; Maria Ulfa; Febriyanti Panjaitan (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2018)
The Palembang City Health Service has implemented the Wireless network as one of the services to connect to the internet, to expand the signal coverage in the City Government Service network, has been implemented wirelessly with a Wireless Distribution System (WDS) system that allows wireless interconnection in access points in the IEEE 802.11 network. This allows wireless networks to be developed using multiple APs (Access points) without having to require a network cable backbone to connect between networks. Users connected to the Hotspot at Palembang City Health Office are increasing year by year. This is seen from the number of access usage needs each year. The analysis that will be carried out on Palembang's health service wireless LAN network uses several parameters, namely Bandwidth, Throughput, Delay, and Packet Loss, where these parameters are used to see the quality of network services (QOS), so that the results of this research will be expected to provide solutions for the service the health of the city of Palembang in evaluating the quality of the network, especially wireless LAN so that it can overcome any problems that occur. Research methods using Action Research or action research is one form of research design, in action research researchers describe, interpret and explain a social situation at the same time by making changes or interventions with the aim of improvement or participation. The results of the QOS parameters are delay according to the TIPHON version, that a very good delay occurs at the Health Service from point 2, that is location 2 to location 3, with a delay of under 150 milli second (ms).